2004
DOI: 10.1176/appi.ajp.161.6.996
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Dysfunction in Antipsychotic-Naive First-Episode Unipolar Psychotic Depression

Abstract: The similar neuropsychological profiles for schizophrenia and psychotic depression suggest that these psychotic disorders may have common pathophysiological features. The dramatic differences in performance between the patients with psychotic depression and those with nonpsychotic depression point to a marked distinction in neurocognitive function associated with the expression of psychosis in depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 37 publications
10
78
0
14
Order By: Relevance
“…This may be explained by differential effects of fatigue (Peters, 1980). Also comma as expected (Bashir et al, 2013;Hill et al, 2004;Hueng et al, 2011;Kertzman et al, 2010;Lampe et al, 2004;Rohling et al, 2002;Swann et al, 1999), we found significant impairment in psychomotor speed between unipolar depressed subjects and controls. Psychomotor performance in depressed subjects may be further influenced by other factors, such as hospitalization status/duration, severity, subtype and duration of depression, and medication (Bashir et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be explained by differential effects of fatigue (Peters, 1980). Also comma as expected (Bashir et al, 2013;Hill et al, 2004;Hueng et al, 2011;Kertzman et al, 2010;Lampe et al, 2004;Rohling et al, 2002;Swann et al, 1999), we found significant impairment in psychomotor speed between unipolar depressed subjects and controls. Psychomotor performance in depressed subjects may be further influenced by other factors, such as hospitalization status/duration, severity, subtype and duration of depression, and medication (Bashir et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Given that motor retardation is a common feature of depression (American Psychiatry Association, 2013;Caligiuri & Ellwanger, 2000), tests of fine psychomotor performance, such as the Finger Tapping Test (FTT), have been widely utilized in several studies on depression (Arnold et al, 2005;Bashir, Khade, Kosaraju, Kumar, & Rani, 2013;Caligiuri & Ellwanger, 2000;Hill, Keshavan, Thase, & Sweeney, 2004;Hueng et al, 2011;Kertzman et al, 2010;Lampe, Sitskoorn, & Heeren, 2004;Meyer et al, 2006;Rohling, Green, Allen, & Iverson, 2002;Schrijvers, Hulstijn, & Sabbe, 2008;Swann, Katz, Bowden, Berman, & Stokes, 1999) proving to be reliable to access impairments and discard malingering (Arnold et al, 2005;Rohling et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors could explain these discrepancies, and among them psychotic features. Indeed, it was observed that patients with first episode of psychotic unipolar depression had a pattern of neuropsychological dysfunction similar to but less severe than that of patients with schizophrenia (Hill et al 2004). This suggests that these psychotic disorders may have common pathophysiological features.…”
Section: Cognitive Deficits In Major Depressionmentioning
confidence: 99%
“…There are considerable data suggesting that PMD is a distinct syndrome from nonpsychotic major depression (NPMD), as evidenced by significant differences on a number of different dimensions: neuropsychological testing Fleming et al, 2004;Hill et al, 2004), response to treatment (Spiker et al, 1985), and morbidity and mortality (Rothschild, 2003;Vythilingam et al, 2003). PMD patients also show a number of biological characteristics that are distinct from NPMD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, they demonstrate excessive hypothalamic-pituitary-adrenal (HPA) axis activity, as evidenced by elevated urinary free cortisol levels (Kathol et al, 1989), elevated evening and night time cortisol levels (Sachar et al, 1973), and high rates of dexamethasone nonsuppression (Nelson and Davis, 1997). Administration of glucocorticoids to healthy controls (Lupien et al, 1999;Newcomer et al, 1999) results in cognitive deficits similar to those seen with PMD Fleming et al, 2004;Hill et al, 2004). In addition, a number of years ago, we hypothesized that the psychotic features of PMD were due to excessive glucocorticoid activity (Schatzberg et al, 1985).…”
Section: Introductionmentioning
confidence: 99%